Status and priority conservation actions for Australian frog species. (July 2020) - Gillespie, Graeme R.; Roberts, J. Dale; Hunter, David; Hoskin, Conrad J.; Alford, Ross A.; Heard, Geoffrey W.; Hines, Harry; Lemckert, Frank; Newell, David; Scheele, Benjamin C.
Abstract: Coherent, multi-species conservation strategies rely on up-to-date assessments of extinction risk, and prioritising and implementing well-founded management and research actions. Using IUCN criteria and methods, we reassessed the conservation status of all 243 Australian frog species. We also identified key threats and associated potential management actions. We subsequently scored the relative value, feasibility and current levels of implementation of all management and research actions for threatened and Data Deficient species. These scores were then used to rank the relative priority of management and research actions, identifying the highest priority actions for reducing extinction risk for Australia's frogs. Our revised assessment identified 45 threatened frog species in Australia, a 10% reduction from the 2004 assessment. However, the number of species assessed as Extinct increased by two, and four species were added to the Critically Endangered list. Improvements in conservation status for some species resulted from better knowledge and natural population stabilisation or recovery following disease impacts, rather than as a consequence of management. Improved knowledge has also resulted in a reduction of Data Deficient species from ten to eight. We found substantial reductions in species extinction risk may be achievable by implementing a relatively discrete set of well-targeted management and research actions. Given its simple and dynamic nature, our method can be regularly updated with new information, and can also be applied at different geographic scales. Our prioritisation will enable improved allocation of limited resources to maximise conservation outcomes for Australian frogs.